2011
DOI: 10.1111/j.1745-4530.2010.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

DEGRADATION KINETICS AND COLOR STABILITY OF SPRAY‐DRIED ENCAPSULATED ANTHOCYANINS FROM HIBISCUS SABDARIFFA L.

Abstract: Dry powder of red color from roselle calyces, which can be used as natural colorant and functional food ingredient, was produced using microencapsulation technique. Four different matrices, i.e., maltodextrin, gum Arabic, combination of maltodextrin and gum Arabic, and soluble starch were used for encapsulation study. Identification and measurement of anthocyanins in encapsulated roselle was made by high‐performance liquid chromatography. Encapsulation efficiencies were determined and compared with storage ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(102 citation statements)
references
References 24 publications
7
88
0
7
Order By: Relevance
“…Idham et al 37 noticed the same trend (decrease in L* and a* values, and increase in b* values during storage) in spray dried encapsulated anhocyanins from Hibiscus sabdariffa. They also concluded that colour changes depend on the type of carriers.…”
Section: Colour Parameters Of Powdersmentioning
confidence: 69%
“…Idham et al 37 noticed the same trend (decrease in L* and a* values, and increase in b* values during storage) in spray dried encapsulated anhocyanins from Hibiscus sabdariffa. They also concluded that colour changes depend on the type of carriers.…”
Section: Colour Parameters Of Powdersmentioning
confidence: 69%
“…The calices of this plant are appreciated for their use in beverages, syrups, jams and concentrates (Cissé et al, 2009;Costa-Rocha et al, 2014). The resulting products have an interesting acidity and a bright red color due to the presence of anthocyanins especially delphinidin and cyanidin 3-D-sambubioside (Chang et al, 2012;Cissé et al, 2009;Idham et al, 2012;Março et al, 2011). Their high content in polyphenolic compounds provides them notable antioxidant and free radical scavenging activities (Mohd-Esa et al, 2010;Serrano-Cruz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After phase separation, the clear supernatant was collected and filtered through a 0.45-mm pore-sized Millipore membrane (IDHAM et al, 2012).…”
Section: Encapsulation Efficiencymentioning
confidence: 99%
“…According to Idham et al (2012), the carrier combination giving the greatest encapsulation efficiency and the effectiveness of the interactions depended on the chemical and physical structure of each support material. Therefore, the use of whey protein concentrate or soy protein isolate combined with modified starch in the formulation has a greater potential to encapsulate the anthocyanins than the carrier agents alone.…”
Section: Encapsulation Efficiencymentioning
confidence: 99%